Juridical Review of Illegal Fishing in Indonesia as Transnational Crime - Supriyono, Supriyono; Prakasa, Satria Unggul Wicaksana (Law Research Review Quarterly, 2021)
Indonesia is an archipelagic state which has a sea area wider than its land area. Where the sea area stores abundant fish resources. This triggers the desire of foreign countries to take part in an illegal way, namely illegal fishing. The theft of fish in Indonesian seas by ships with foreign flags has violated the sovereignty and is detrimental to Indonesia economically, socially, and ecologically. The Ministry of Maritime Affairs and Fisheries noted that illegal fishing has resulted in state losses of up to the US $ 24-30 billion per year. Illegal fishing is a fishery crime and is a form of transnational crime because its elements involve more than one country, namely planning, preparation, and the consequences of this crime, involving more than one country. So that the practice of illegal fishing must be prevented and eradicated as soon as possible because the natural wealth in the sea must be protected for the maximum benefit of the people. Illegal fishing regulations are contained in national law and international conventions